Recognition of emplacement time of Jambil carbonatites from NW Pakistan: constraints from fission-track dating of apatite using age standard approach (the ζ method) - Khattak, N. U.; Akram, M.; Ullah, K.; Qureshi, A. A.; Qureshi, I. E. (Journal of Himalayan Earth Sciences, 2004)
A group of alkaline igneous complexes, the Peshawar Plain Alkaline Igneous Province (PAIP), is exposed in an arcuate fashion north of the Peshawar Plain in NW Pakistan. The PAIP, which extends for about 150 km, from Tarbela in the east up to Loe-Shilman near the Pakistan-Afghanistan border in the west, consists mainly of granites. syenites, gabbros, ijolites and carbonatites. The carbonatites are present in Loe-Shilman, Sillai-Patti, Jawar, Jambil, Koga and Tarbela. The Jambil carbonatite deposit occurs as small isolated bodies and plugs of carbonatites and fenites exposed in Jambil area, about 10 km SE of Mingora in lower Swat. Here the carbonatite bodies intrude the Swat granitic gneisses and Manglaur Formation. Conduction of fission-track dating studies on the apatite crystals using the external detector method and age standard approach (the method) yielded a pooled age of 29.3 ± 1.2 Ma and an average age of 290 ± 1.2 Ma for the Jambil carbonatite of lower Swat area. These ages are concordant with the fission track age of 32.1 ± 1.9 Ma on zircon from the Sillai Patti carbonatite, fission track age of 29.1 ± Ma on apatite from the Jawar carbonatite. K-Ar dates of 31 ± 2 Ma on biotites from the Loe-Shilman and Sillai Patti carbonatites, U-Pb age of 29.26 ± O. 12 Ma on zircon from one of the alkaline pegmatitic dykes of lower Swat area and Ar-Ar age of 28.4 ± 1.1 Ma on muscovite from the same dyke of the earlier workers. This relationship confirms that the fission-track apatite age of this study is the emplacement age. This strongly suggests the occurrence of an Oligocene alkaline magmatic episode within the region.